2005
DOI: 10.1073/pnas.0502548102
|View full text |Cite
|
Sign up to set email alerts
|

Thinning of the cerebral cortex visualized in HIV/AIDS reflects CD4 + T lymphocyte decline

Abstract: HIV͞AIDS infection is the fourth leading cause of death worldwide, and one in every 100 adults aged 15-49 years is HIV-infected. Forty percent of AIDS patients suffer from neurological symptoms, but the selective profile of damage caused by HIV in the brain is not well understood. Here, we report 3D maps revealing how AIDS affects the human cerebral cortex, identifying the most vulnerable regions and where deficits link with cognitive decline and immunesystem suppression. With high-resolution brain MRI scans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
275
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 290 publications
(312 citation statements)
references
References 26 publications
32
275
4
1
Order By: Relevance
“…Thus, ERS activity detected in the right DLPFC and FEF of controls potentially reflects neural activity serving low-level attentional control (i.e., right DLPFC) of processes that maintain or control eye-position in the visual field. Finally, Thompson et al showed that the degree of cognitive impairment in non-demented HIV-infected patients was strongly correlated with the thickness of the DLPFC [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ERS activity detected in the right DLPFC and FEF of controls potentially reflects neural activity serving low-level attentional control (i.e., right DLPFC) of processes that maintain or control eye-position in the visual field. Finally, Thompson et al showed that the degree of cognitive impairment in non-demented HIV-infected patients was strongly correlated with the thickness of the DLPFC [30].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 With the advent of highly-active antiretroviral therapy (HAART) in the mid-to-late ’90s, 11 the neurocognitive sequelae of HIV have lessened in severity 1214 and become somewhat more variable in expression, 15 although mild neurocognitive deficits persist. 13,1619 Although the current cognitive impairment-profile of HIV is relatively mild for many individuals, it is nonetheless predictive of significant decline in daily functioning.…”
mentioning
confidence: 99%
“…However, individuals continue to experience significant CNS disturbances. Recent evidence provided by Thompson et al (2005) demonstrated the impressive extent to which HIV exerts deleterious effects on the CNS, even during successful HAART treatment. The authors reported several brain regions to be reduced as much as 15% in volume.…”
Section: Discussionmentioning
confidence: 99%